Retracted: Investigating Preschool Children’s Behavioral and Emotional Problems Using Pediatric Symptom Checklist (PSC 17) During Distance Learning in Pandemic Covid-19 - Teguh Fachmi; Dalis Ravida Kustiwa; N Umi Hani (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2022)
RETRACTION TO: Fachmi, T., Kustiwa, D. R., Hani, N. U. (2022). INVESTIGATING PRESCHOOL CHILDREN’S BEHAVIORAL AND EMOTIONAL PROBLEMS USING PEDIATRIC SYMPTOM CHECKLIST (PSC 17) DURING DISTANCE LEARNING IN PANDEMIC COVID-19. Cakrawala Dini: Jurnal Pendidikan Anak Usia Dini, 13(2), 89-94.This article has been retracted by Publisher based on the following reason:The Editor of Cakrawala Dini: Jurnal Pendidikan Anak Usia Dini found the double publication in the article publishing due to article's content similarity published in https://ejournal.undiksha.ac.id/index.php/JJPAUD/article/view/49307Fachmi, T., Kustiwa, D. R., Hani, N. U. (2022). Preschool Children’s Behavioral and Emotional Problems using Pediatric Symptom Checklist (PSC 17) during Distance Learning. Jurnal Pendidikan Anak Usia Dini Undiksha, 10(2).One of the conditions of submission of paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process